Blocos de concreto para pavimentação produzidos com rejeito de mineração e cinzas de bagaço de cana de açúcar - Salgado, Lívia de Melo (2018)
Mining waste from ore beneficiation is considered a problem for mining companies, although it is not harmful, the treatment, storage and management of this solid waste are factors that demand attention. The objective of this work was to evaluate the effect of the use of mining tailings and cane bagasse ash (CBC) on the properties of concrete pavers (Pavers). The composite materials of the mixture (cement, medium sand, mining tailings and sugarcane bagasse ash) were characterized as the physical, morphological and granulometric properties. The trait used for the control treatment was 1: 2.98: 3.49: 2.21 (cement: sand: stone powder: gravel). The efficiency of the replacement of 0%, 20%, 40%, 60%, 80% and 100% of the sand aggregate by the mining tailings was evaluated, and the effect of replacing 1% cement with ash sugar cane bagasse. The pavers were produced in a vibro compression machine and were cured for 28 days at room temperature, after which their physical and mechanical properties were evaluated by means of density, water absorption (NBR 9781), compressive strength (NBR 9781) and scanning electron microscopy before and after accelerated aging (NBR 13554). The results of the tests carried out prove the feasibility of replacing 100% of the sand by the mining tailings in the production of the floors, which can not be considered for the use of sugarcane bagasse ashes, which compromised the evaluated properties.